Pendampingan Masyarakat Kelompok Tani dalam Upaya Antisipasi Serangan Virus Tungro Pada Tanaman Padi di Pulau Lombok - Fitasari, Baiq Diah; Rengganis, Baiq Santi; Fathurrahman, Fathurrahman (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This community service activity aims to increase the knowledge and capacity of farmer groups in preventing the spread of the tungro virus which inhibits the production of their rice plants. The method of implementing this service uses interactive counseling and mentoring. The partner of this activity is the Tandur Rinjani Farmers Group located in Wajagesang Village, Central Lombok Regency. The evaluation instruments used in this activity are structured interviews, field observations and documentation to deepen information about farmers' experiences during mentoring, observing the direct application of anticipation techniques in the field, and analyzing written data from farmer group records. The results of this community service are an increase in the understanding of farmer groups regarding the tungro virus and encouraging them to implement sustainable preventive measures. In addition, this service program has succeeded in increasing the understanding and skills of farmer groups in agricultural product management, from storage, processing, packaging, to marketing. By implementing good product management techniques, farmer groups are able to improve the quality and competitiveness of their products in the market, as well as open access to a wider market.